2020
DOI: 10.1186/s40648-020-00158-1
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatically-driven stretching machine for ankle dorsiflexion: safety concepts and effectiveness test involving healthy young subjects

Abstract: Stretching is a major treatment for restoring the ankle range of motion while decreasing the ankle stiffness. An automatic stretching machine can provide long-term continual stretching at home. However, no commercial stretching machines are currently available, and therefore, no safety guidelines exist for them. In this study, we prototyped a stretching machine using a chassis from a commercial foot exerciser for preventing disuse syndrome, and then proposed three safety concepts as general requirements for st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Yamada et al developed a machine for 3D foot motion for dorsiflexion, abduction, and eversion using McKibben-type pneumatic actuators and wire-driven mechanisms Kimura et al, 2017). The authors of the present study have also developed an ankle stretching machine by modifying a commercial foot exerciser with a pneumatic actuator (Shiraishi et al, 2020) and demonstrated its effectiveness in decreasing the passive dorsiflexion resistance in young healthy subjects. In the present study, we use this developed machine.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…Yamada et al developed a machine for 3D foot motion for dorsiflexion, abduction, and eversion using McKibben-type pneumatic actuators and wire-driven mechanisms Kimura et al, 2017). The authors of the present study have also developed an ankle stretching machine by modifying a commercial foot exerciser with a pneumatic actuator (Shiraishi et al, 2020) and demonstrated its effectiveness in decreasing the passive dorsiflexion resistance in young healthy subjects. In the present study, we use this developed machine.…”
Section: Introductionmentioning
confidence: 79%
“…The stretching machine ( Fig. 1) was based on the chassis of a commercial foot exercise machine for ankle dorsi/ plantarflexion (Shiraishi et al, 2020). When the bellows (i.e., pneumatic actuator) were pressurized, it expanded in the longitudinal direction, and the foot was dorsiflexed with rotation of the moving part of the machine (Fig.…”
Section: Ankle Stretching Machinementioning
confidence: 99%
See 2 more Smart Citations
“…In a future work, the foot-stretching technique used by each physical therapist and its effectiveness for the patient should be analyzed simultaneously to establish an effective stretching method. Moreover, several previous studies developed automatic machines for ankle stretching 15 , 16 , 17 , 18 ) . Although currently, no such machine has been commercialized, the analysis of foot-stretching techniques in this study will help in their development.…”
Section: Discussionmentioning
confidence: 99%